EXPLORATION OF ETHNOMATHEMATICS IN TRADITIONAL HOUSE ORNAMENTS PAKPAK AS A REPRESENTATION OF MATHEMATICS IN CULTURE - pratiwi, windi ariani; Mandasari, Lola (Prima: Jurnal Pendidikan Matematika, 2025)
The research conducted is titled “Exploration of Ethnomathematics in Pakpak Traditional House Ornaments as a Representation of Mathematics in Culture,” which is based on the fact that Pakpak traditional houses have ornaments that are used to provide beauty and a belief in protecting the people who live in Pakpak traditional houses from evil forces. The current state of Pakpak traditional houses is such that they are very difficult to find. A few still stand in remote villages in Pakpak Bharat Regency, notably in Salak II Village. These traditional houses are now used as recreational sites for tourists and local residents, though some are left to decay and remain uninhabited. The research methodology employed a qualitative approach with an ethnographic perspective. Data and sources were collected through primary and secondary data. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted using data reduction, data presentation, and conclusion drawing/data verification. The research findings revealed the presence of concepts related to plane geometry, similarity, and geometric transformations. The concepts of plane geometry found in the ornaments of traditional Pakpak houses include squares, triangles, rectangles, trapezoids, pentagons, and circles. Based on the findings of the above research, the ornaments found in traditional Pakpak houses have their own meanings. The ornaments found in traditional Pakpak houses contain mathematical concepts.